PEDAGOGICAL CONDITIONS OF FORMATION OF PEDAGOGICAL CULTURE OF STUDENTS (Pedagogy of Higher and Secondary Education, 2010)
In article pedagogical conditions of formation pedagogical culture of the student higher educational institution are considered during training.